2008
DOI: 10.1074/jbc.m707111200
|View full text |Cite
|
Sign up to set email alerts
|

S1 Ribosomal Protein Functions in Translation Initiation and Ribonuclease RegB Activation Are Mediated by Similar RNA-Protein Interactions

Abstract: The ribosomal protein S1, in Escherichia coli, is necessary for the recognition by the ribosome of the translation initiation codon of most messenger RNAs. It also participates in other functions. In particular, it stimulates the T4 endoribonuclease RegB, which inactivates some of the phage mRNAs, when their translation is no longer required, by cleaving them in the middle of their Shine-Dalgarno sequence. In each function, S1 seems to target very different RNAs, which led to the hypothesis that it possesses d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
53
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(71 citation statements)
references
References 49 publications
15
53
2
Order By: Relevance
“…Consistent with this assignment, NMR studies on truncated S1 with only D3-5 showed that even in the absence of RNA, D4 and D5 are tightly associated, whereas D3 is loosely connected to D4 (40). When binding to RNA, there is a conformational change of the linker between D3 and D4, and all three domains bind to the RNA with similar RNA-protein interactions (40). Based on the results described above, we propose a minimum model for S1 interaction with RNA secondary structures (Fig.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Consistent with this assignment, NMR studies on truncated S1 with only D3-5 showed that even in the absence of RNA, D4 and D5 are tightly associated, whereas D3 is loosely connected to D4 (40). When binding to RNA, there is a conformational change of the linker between D3 and D4, and all three domains bind to the RNA with similar RNA-protein interactions (40). Based on the results described above, we propose a minimum model for S1 interaction with RNA secondary structures (Fig.…”
Section: Discussionsupporting
confidence: 51%
“…To complete a 10 nt total binding size, the hidden step would be from binding of another single RNA-binding domain. Consistent with this assignment, NMR studies on truncated S1 with only D3-5 showed that even in the absence of RNA, D4 and D5 are tightly associated, whereas D3 is loosely connected to D4 (40). When binding to RNA, there is a conformational change of the linker between D3 and D4, and all three domains bind to the RNA with similar RNA-protein interactions (40).…”
Section: Discussionmentioning
confidence: 49%
“…The modern chloroplast maintains a circular genome and transcription and translation machinery similar to that of its evolutionary precursor [74], [75]. In E. coli , ribosomal protein S1 contains six S1 domains that are essential for RNA binding and is an essential protein required for the translation of most transcripts [57], [59], [60]. Based on the molecular diversity analysis, RPS1s in prokaryotes have been classified into four types depending on their functional reliability of translation initiation [58].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we have identified chloroplast ribosomal protein S1 (RPS1) as a heat-responsive protein through proteomic screening of heat-responsive proteins. In Escherichia coli , RPS1, the largest ribosomal protein, is involved in the process of mRNA recognition and binding by the 30S ribosomal subunit to the translation initiation site [57][59]. The RPS1 in E. coli consists of six repetitions of a conserved structural domain, called S1 domain, which is found in many other proteins involved in RNA metabolism in all organisms [57], [58].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation